Functional P2X7 receptor polymorphisms (His155Tyr, Arg307Gln, Glu496Ala) in patients with crohn's disease - Haas, Stephan; Ruether, A.; Singer, Manfred V.; Schreiber, S.; Böcker, Ulrich (Scandinavian journal of immunology, 2007)
Genetic factors contribute to inflammatory bowel diseases. Recently, the P2X7 receptor was found to be a key player in caspase-1-mediated processing of the proinflammatory cytokines, interleukin-1β and interleukin-18. We therefore aimed to determine whether the gain-of-function single nucleotide polymorphism (SNP) His155Tyr and the loss-of-function SNP Arg307Gln and Glu496Ala were associated with susceptibility to Crohn's disease (CD). For association analysis, 681 unrelated CD patients and 736 healthy controls were enrolled. Furthermore, 490 CD trios were included for segregation analysis. Genotyping was performed by the application of the TaqMan® MGB biallelic discrimination system. The Arg307Gln polymorphism revealed a borderline significant difference in genotype frequencies between CD patients and controls (P = 0.06) without implying any pathological significance because of low case numbers. Case-control statistics for the variants His155Tyr and Glu496Ala showed no association with CD phenotype (P = 0.19 and 0.99). Subsequent family-based transmission disequilibrium test did not prove an association of the investigated single-nucleotide polymorphisms with CD. In conclusion, the analysed intragenetic variants of the P2X7 receptor may not be a susceptibility factor for CD.